Balloon mitral valvotomy in youngest documented rheumatic mitral stenosis patient. Issue 5 (27th May 2015) - Sarkar, Achyut; Patil, Shailesh; Ahmed, Imran
<x xml:space="preserve">Abstract</x> Juvenile rheumatic mitral stenosis (MS) is common in the Indian subcontinent. Early recognition and management is essential. Rarely rheumatic MS may occur in <5 years of age, wherein rapid hemodynamic progression and cardiac morbidity and mortality occurs. Severe/symptomatic MS in preschool age requires urgent and meticulous decision making. Condition of valve and wishes of parents may complicate management decisions. Percutaneous transmitral commissurotomy (PTMC) may, therefore, become the only life‐saving intervention in these cases unless contraindicated, although the procedure entails considerable technical issues in this age group. Herein, we report a successful balloon mitral valvotomy in a 4‐year‐old child with severe rheumatic MS (documented since 2 years 6 months of age) presenting with repeated pulmonary edema. To the best of our knowledge, this child is the youngest documented case of established rheumatic heart disease and also one of the youngest PTMC procedure performed. This report supports the clinical usefulness of PTMC in childhood MS; however, pertinent technical issues are raised, which needs a proper consensus. © 2015 Wiley Periodicals, Inc.